Evaluating the Beneficial and Detrimental Effects of Bile Pigments in Early and Later Life - Dennery, Phyllis A. (Frontiers in Pharmacology, 2012)
The heme degradation pathway has been conserved throughout phylogeny and allows for the removal of a pro-oxidant and the generation of unique molecules including bile pigment with important cellular functions. The impact of bile pigments on health and disease are reviewed as is the special circumstance of neonatal hyperbilirubinemia. In addition, the importance of promoter polymorphisms in the UDP-glucuronyltransferase gene (UGTA1), which is key to the elimination of excess bilirubin and to preventing its toxicity, are discussed. Overall, the duality of bile pigments as either cytoprotective or toxic molecules is highlighted.